Complete genome sequence analysis of dengue virus type 2 isolated in Brunei - Osman, O.; Fong, M.Y.; Devi, S. (Elsevier, 2008)
In a previous study, we have reported the detection and isolation of dengue virus in Brunei (Osman, O., Fong, M.Y., Devi, S., 2007. A preliminary study of dengue infection in Brunei. JJID 60 (4), 205-208). DEN-2 was the predominant serotype followed by DEN-1. The full genomic sequences of 3 DEN-2 viruses isolated during the 2005-2006 dengue incident in Brunei were determined. Twenty-five primer sets were designed to amplify contiguous overlapping fragments of approximately 500-600 base pairs spanning the entire sequence of the viral genome. The amplified PCR products were sent for sequencing and their nucleoticles and the deduced amino acids were determined. All three DEN-2 virus isolated were clustered in the Cosmopolitan genotype of the DEN-2 classification by Twiddy et al. This work constitutes the first complete genetic characterization of three Brunei DEN-2 virus strains. (c) 2008 Elsevier B.V. All rights reserved.